The Tobacco-Free Village Program: Helping Rural Areas Implement and Achieve Goals of Tobacco Control Policies in India - Chatterjee, Nilesh (Glob Health Sci Pract, 2017)
India has 274 million tobacco users and a tobacco use prevalence of 38% in rural areas. Tobacco consumption causes 1 million deaths and costs the health system nearly US$23 billion annually. Tobacco control policies exist but lack proper implementation. In this article, we review the Tobacco-free Village (TfV) program conducted in Maharashtra state in India and describe its process to help villages in rural India achieve “tobacco-free” status (i.e., the sale and use of tobacco are prohibited by law). We reviewed program documents and conducted 22 qualitative interviews with program staff and village-level stakeholders. From 2008 to 2014, Salaam Mumbai Foundation implemented the TfV program in 60 villages in Maharashtra state. The program used a number of strategies to help villages become tobacco free, including collaborating with a community-based organization, leveraging existing health workers, conducting a situation analysis, training health workers, engaging stakeholders, developing TfV assessment criteria, mobilizing the community, conducting health education, imposing sanctions, and offering incentives. By 2014, 4 villages had achieved tobacco-free status according to 11 assessment criteria. Successful villages demonstrated strong local leader involvement, ownership of the program, and commitment to the cause by residents. The TfV program faced barriers including poor motivation of health workers, difficulty in changing social norms of tobacco use, and refusal of local vendors to stop tobacco sales due to financial losses. This low-cost, community-driven program holds promise for helping public health practitioners and governments implement and achieve the goals of tobacco control policies, especially in resource-scarce settings.